Public Procurement Practices and User Satisfaction in Kabale District: A Case Study of Kabale District Local Government. - Kyakunzire, Furumera (Kabale University, 2025)
The study examined the Public procurement practices and user satisfaction in Kabale District. A case study of Kabale District Local Government. The study was guided by three objectives to examine the effect of transparency on user satisfaction in Kabale District Local Government; to establish the effect of non-discriminatory procurement practices on user satisfaction in Kabale District Local Government, to analyze the effect of competition on end-user satisfaction in Kabale District Local Government. The study used a descriptive research design that aimed at generating information after the incident had occurred; the Qualitative approach included the use of interviews. Data was collected using a questionnaire and interview guide, and simple random and purposive sampling methods were used. Both qualitative and quantitative methodologies were used to analyze data as a sample size of 59 respondents was used. The study revealed the effect of transparency on user satisfaction in Kabale District Local Government and these included helping to avoid any possible selection process manipulation, promoting the efficient and effective use of public resources, promoting competition, openness, and accountability in public procurement, helping to determine the effectiveness of a procurement system, transparent tools are necessary to foster long-lasting confidence, transparency is an important component of good governance. The study revealed the factors that the effect of non-discriminatory procurement practices on user satisfaction in Kabale District Local Government and these included the demand for enhanced Transparency and Trust, improved Quality of Services, enhanced Social Equity, regulatory Compliance, enhanced economic benefit, procurement system is robust and effective when it has a clear legal governing structure. Lastly, the study revealed there the effects of competition on user satisfaction in Kabale district local government and these included enhanced Choice for Users, cost Efficiency, innovation and Responsiveness, increased Accountability and Transparency, and improved Quality of Services.